DESAIN KEMASAN SEKUNDER PADA PRODUK PROL TAPE DENGAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) (Studi Kasus di UD. Purnama Jati, Kabupaten Jember) - Ida Bagus Suryaningrat; Nidya Shara Mahardika; Mela Eriana Firlanarosa (Faculty of Agricultural Technology, University of Jember, 2021)
Packaging refers to an object to protect and secure certain products within the package as well as giving a particular image to persuade the customers. The research objectives were to identify customers’ desires and satisfaction levels to prol tape product packaging using the quality function deployment (QFD) method, designing packages, determining the type of packaging, and determining the compressive strength of the packaging using a universal testing machine (UTM). The research findings were 4 important attributes found for secondary packaging, namely the attributes of strength, appearance, price, and protection. Based on the attributes, the researcher designed a new secondary packaging using the RSC (regular slotted container) type of packaging consisting of two parts; BC flute type for outer packaging and B flute type for inner packaging. Meanwhile, the old secondary packaging only consisted of one part, namely B flute type for outer packaging. According to the compressive strength test results, the new packaging has a compressive strength value of 189.6 kgf with a maximum stack number of 40 stacks, and the old packaging has a compressive strength value of 82.7 kgf with a maximum stack number of 18 stacks. Keywords: compressive strength, packaging, prol tape, QFD